Modelling considerations for cave compaction at New Afton Mine - Cancino, C; Fuenzalida, MA; Kamp, C (Caving 2022: Fifth International Conference on Block and Sublevel Caving, 2022)
New Afton is a block caving mine located 10 km outside of Kamloops, British Columbia, Canada. The mine operates two lifts, Lift 1 and B3, with two separate caves on Lift 1, the West Cave (WC) and the East Cave (EC). Lift 1 and B3 production levels are located approximately 600 m and 760 m below the ground surface. New Afton has a unique combination of geometric geotechnical conditions when compared to other cave mines, including: 1) a narrow and long footprint; 2) faulted and poor ground areas; and 3) a high horizontal induced stress environment. During mining of the EC, where a majority of the poor rock mass conditions exist, after the cave was propagated through to surface, local areas of the footprint experienced severe damage and high tunnel convergence, which led to some areas being difficult to access and routinely mine. Because of this, the caved and fragmented material located on top of these drawpoints has experienced a high degree of caved rock compaction over time. New Afton was able to successfully rehabilitate much of these areas while observing compacted cave material, but in addition, a Front Cave Recovery Level (FC) was designed 20 m below a section of the EC production level with the purpose of mining the reserves below and recovering supplemental reserves left by the drawpoints. Cave propagation within compacted cave material requires additional consideration when being used in modelling. A methodology to consider compaction within the EC was proposed using the IMASS model. Assuming two different degrees of compaction for the pre-existing EC, the FC was then assessed with a coupled modelling approach using FLAC3D and REBOP to simulate both the draw/flow and caving propagation to determine abutment stresses and cave loads induced on the production level as material was drawn. It was found that having different degrees of compaction significantly affected the predicted caving rate and cave geometry, affecting ultimate recovery.
Keywords: numerical modelling; cave compaction; cave propagation; Front Cave; recovery level